A randomised controlled trial of triple antiplatelet therapy (Aspirin, Clopidogrel and Dipyridamole) in the secondary prevention of stroke: safety, tolerability and feasibility - Sprigg, Nikola; Gray, Laura J.; England, Timothy J.; Wilmot, Marc R.; Zhao, Lian; Sare, Gillian M.; Bath, Philip M.W. (2008)
Background: Aspirin, dipyridamole and clopidogrel are effective in secondary vascular prevention. Combination therapy with three antiplatelet agents might maximise the benefit of antiplatelet treatment in the secondary prevention of ischaemic stroke.